(untitled) (TAMADDUN NURI JURNALI, 2024)
This article presents theoretical and practical insights into the importance of employing modern approaches in planning, organizing, conducting, and ultimately analyzing and concluding archaeological research. It emphasizes the significance of using advancements in modern technical equipment and computer software in the field of archaeology.